Teacher expectations and differential treatment their effects students' motivation to learn. - Capunsan, Ernita Flavia D.
This study is to determine the effects of teacher expecation and differential treatment on students motivation to learn. The sample was composed of 60 students enrolled in Psychology 101 during the Second Semester on Academic Year 1999-2000. The participants were chosen through simple random sampling. A five-point Likert scale was used to measure the effects of teacher expectation and differential treatment to motivation to learn. Analysis of Variance will be used at a .05 level of significance. The results of the study show that teacher expectation and differential treatment does not affect students' motivation to learn. thus our three hypotheses 1) There are differences in the effects of of the different levels of teacher expectation on students' motivation to elarn, 2) There differences in the different levels of differential treatment on students' motivation to learn and 3) There are differences in the interaction effects of the different levels of teacher expectation and differential treatment on students' motivation to learn. Therefore, the three hypotheses were rejected.